Hubert Fichte, “Paleta”, Paletians, Homosexuals and Other BEATians or: Can’t BEing Be Without Heteronormative Compulsions? - Petrović Jilih Marina М. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Building on the current literary and scientific discourse of the German-speaking area, which only began to deal intensively with issues of gender and queer literature at the end of the twentieth and beginning of the twenty-first century, this paper reveals and analyzes the homosexual and gender discourse presented in the auto-fictional novel Paleta by homosexual/bisexual author Hubert Fichte. The novel was published in 1968 when homosexual relationships were illegal in the Federal Republic of Germany. The goals of the paper are to investigate the (im)possibility of finding self-knowledge, self-stabilization, and happiness in people who are “different” from others, as well as to shed light on the author’s role as a forerunner of contemporary gender and queer studies. The paper is theoretically based on post-feminist theories, which hold that gender is a culturally established construct of heteronormative societies.